Cold hardiness increases with age in juvenile Rhododendron populations - Lim, Chon-Chong; Krebs, Stephen L.; Arora, Rajeev (Frontiers in Plant Science, 2014)
Winter survival in woody plants is controlled by environmental and genetic factors that affect the plant's ability to cold acclimate. Because woody perennials are long-lived and often have a prolonged juvenile (pre-flowering) phase, it is conceivable that both chronological and physiological age factors influence adaptive traits such as stress tolerance. This study investigated annual cold hardiness (CH) changes in several hybrid Rhododendron populations based on Tmax, an estimate of the maximum rate of freezing injury (ion leakage) in cold-acclimated leaves from juvenile progeny. Data from F2 and backcross populations derived from R. catawbiense and R. fortunei parents indicated significant annual increases in Tmax ranging from 3.7 to to 6.4 C as the seedlings aged from 3 to 5 years old. A similar yearly increase (6.7° C) was observed in comparisons of 1- and 2-year-old F1 progenies from a R. catawbiense x R. dichroanthum cross. In contrast, CH of the mature parent plants (> 10 years old) did not change significantly over the same evaluation period. In leaf samples from a natural population of R. maximum, CH evaluations over two years resulted in an average Tmax value for juvenile 2- to 3- year- old plants that was 9.2 C lower than the average for mature (~30 years old) plants. . A reduction in CH was also observed in three hybrid rhododendron cultivars clonally propagated by rooted cuttings (ramets) - Tmax of 4-year-old ramets was significantly lower than the Tmax estimates for the 30- to 40-year-old source plants (ortets). In both the wild R. maximum population and the hybrid cultivar group, higher accumulation of a cold-acclimation responsive 25kDa leaf dehydrin was associated with older plants and higher CH. The feasibility of identifying hardy phenotypes at juvenile period and research implications of age-dependent changes in CH are discussed.